Polymer nanocomposites in high voltage electrical insulation perspective: a review - Lau, Kwan Yiew (Plastics Rubber Institute of Malaysia (PRIM), 2011)
Polymer nanocomposites have attracted wide interests in various industries. This new class of material is capable of providing significant improvements in combined electrical, thermal and mechanical properties. Although the potential use of polymer nanocomposites in electrical insulating industry has only recently begun to be explored, a great number of researches have been conducted with regards to high voltage electrical insulation performance. However, it is found that the fundamental physics and chemistry concerning the property enhancement due to the incorporation of nanocomposites is still poorly understood, and there is still room for improvement in this research area. This paper serves to highlight some of the past developments of polymer nanocomposites and to inspire some potential fields that can be explored in high voltage electrical insulation perspective. Effect of the electrical discharges that causes the surface tracking and partial discharge phenomena on the polymer nanocomposites are the main subjects to be discussed in this paper